Personality Traits and Academic Motivation of Students with Behavior Concerns in a Catholic High School - Mariano, MSLT, Rita G.; Maravilla, Ma. Wilma M. (Philippine Social Science Journal, 2020)
Personality Traits reflect people’s characteristic patterns of thoughts, feelings, and behaviors. The traits relevant to personality are considered to be steady throughout the work of life as suggested in the Five-Factor Model, which identifies any of the five traits a person may exhibit, namely Openness to experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism (OCEAN). On the other hand, academic motivation is the student’s desire, as reflected in his approach, persistence, and level of interest regarding academic subjects when his competence is judged against a standard of performance. Students with behavior concerns are those who underwent disciplinary action due to misdemeanor. Their delinquency may be related to their personality traits, demographics, or lack of academic motivation. Hence, the paper identified the dominant personality traits and assessed 40 male high school students’ academic motivation with behavior concerns in a Catholic school in Antique during the School Year 2019-2020. Likewise, it explores the difference in academic motivation level when grouped according to demographic variables, namely, family monthly income, family structure, and type of misdemeanor. Also, it determines the relationship between personality traits and academic motivation of students with behavior concerns.